2003
DOI: 10.1079/ber2003249
|View full text |Cite
|
Sign up to set email alerts
|

Genetic delineation of sibling species of the pest fruit fly Bactocera (Diptera: Tephritidae) using microsatellites

Abstract: Using a large set of microsatellites, the genetic relationships between three closely related Australian fruit fly species, Bactrocera tryoni (Froggatt), B. neohumeralis (Hardy) and B. aquilonis(May) were investigated. Bactrocera tryoni and B. neohumeralis are sympatric, while B. aquilonisis allopatric to both. The sympatric species, B. tryoni and B. neohumeralis, were found to be genetically distinct. It is likely that despite differences in mating time between these two species, some gene flow still occurs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 15 publications
(25 reference statements)
3
47
0
Order By: Relevance
“…The microsatellites used are detailed in Kinnear et al . (1998) and Wang et al (2003). We tested for clustering among the outbreak flies using both correspondence analysis (CA) and the Structure software (Pritchard et al .…”
Section: Microsatellite Typing and Analysismentioning
confidence: 99%
“…The microsatellites used are detailed in Kinnear et al . (1998) and Wang et al (2003). We tested for clustering among the outbreak flies using both correspondence analysis (CA) and the Structure software (Pritchard et al .…”
Section: Microsatellite Typing and Analysismentioning
confidence: 99%
“…With microsatellite markers having been isolated for these species (Kinnear et al 1998;Wang et al 2003), we revisited the question of the origin of these wild intermediates. An earlier study has shown that the two species can be differentiated using microsatellites, but that they are closely related (F ST ∼ 0.1; Wang et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This means that on the average, the populations were 49 % deficient of heterozygotes. HWE deviations as a result of heterozygote deficiency may be attributed to null alleles, inbreeding, finite sample size, a chance of sampling effect or the combination of subpopulations (Aketarawong et al, 2006;Wang et al, 2003;Dai et al, 2004;Augustinos et al, 2005). Some samples failed to yield PCR products at loci Bd39, Bd43B, and Bd76 but they were successfully amplified at other loci, suggesting the existence of null alleles at these loci.…”
Section: Resultsmentioning
confidence: 99%